Intensive care nurses' implicit and explicit attitudes and their behavioural intentions towards obese intensive care patients. (7th October 2019) - Robstad, Nastasja; Westergren, Thomas; Siebler, Frank; Söderhamn, Ulrika; Fegran, Liv
Abstract: Aims: To examine qualified intensive care nurses' implicit and explicit attitudes towards obese intensive care patients and whether their attitudes are associated with their behavioural intentions towards these patients. Background: Obese intensive care patients may experience more stress than do normal‐weight patients. Intensive care nurses' attitudes and the way they address their care are thus vital. Despite a range of studies revealing that health professionals hold anti‐fat attitudes towards obese patients, there is a lack of knowledge about intensive care nurses' implicit and explicit attitudes and if such attitudes are associated with behavioural intention. Design: A cross‐sectional survey. Methods: From November 2017 ‐ January 2018, a web‐based survey was conducted with 159 qualified intensive care nurses (84.3% women, mean age 45.52 years) recruited through 16 intensive care units and Facebook. The survey consisted of implicit attitude tests, explicit bias scales, the Anti‐fat Attitude questionnaire, vignettes measuring behavioural intention, and demographic questions. Results: Intensive care nurses reported implicit preferences for thin over thick people and found obese individuals slightly 'worse' and 'lazy', comprising less willpower than thin individuals. Attitudes were not associated with behavioural intention. Conclusion: This study provides new knowledge about qualified intensive care nurses' anti‐fat attitudes and behavioural intention towards obese intensive care patients. These findings should be acknowledged by policymakers, clinical healthcare providers and educators to secure optimal care for these patients. Impact Statement: These results should be used in nursing attitude change programmes, in intensive care units, and among nursing educators, focusing on increasing nurses' knowledge of the complexities of obesity. Further research on obese intensive care patients' healthcare experiences and the impact that healthcare providers' anti‐fat attitudes and behaviours has on patients' perceived care quality is needed. Abstract : 目的: 探讨合格的重症监护护士对肥胖重症监护患者的内隐态度和外显态度, 以及其态度是否与其对肥胖重症监护患者的行为意图相关。 背景: 肥胖重症监护患者可能会比正常体重的患者承受更多压力。重症监护护士的态度及其处理护理的方式尤为重要。尽管一系列研究表明, 卫生专业人员对肥胖患者持反对肥胖的态度, 但对于重症监护护士的内隐态度和外显态度, 以及这些态度是否与行为意图有关仍缺乏了解。 设计: 一项横断面研究 方法: 自2017年11月至2018年1月, 我们通过16个重症监护室和Facebook招募了159名合格的重症监护护士(84.3%的女性, 平均年龄45.52岁), 并对这些护士进行了网络调查。此调查包括内隐态度测试、外显偏见计量表、反肥胖态度问卷、衡量行为意图的插图以及人口统计学问题。 结果: 重症监护护士报告, 相比于肥胖的患者, 其对较瘦的患者存在隐性偏爱, 因为他们发现肥胖患者较"差"和"懒", 肥胖患者意志力比瘦弱的患者更弱。其态度与行为意图无关。 结论: 此研究对合格的重症监护护士对肥胖重症监护患者的反肥胖态度以及行为意图提出了新的认知。政策制定者、临床医务人员和教育人员应认可此次调查结果, 从而确保为肥胖重症监护患者提供最佳护理。 影响陈述: 这些结果应用于护理态度转变计划、重症监护病房以及护理教育工作者中, 着重于增加护士对过度肥胖复杂性的了解。进一步研究肥胖重症监护患者的医疗体验, 以及医护人员的反肥胖态度和行为对患者感知到的护理质量的影响。